Engineering Design and Feasibility Analysis of Geothermal-heated Swimming Pool in Lembang, West Java - Lukmana, Allen Haryanto; Prasetyo, Rizqi Mahfudz; Rifani, Ria Ayu (Journal of Earth Energy Engineering, 2020)
A heated swimming pool has long been known as a tourist destination, sports, to stress therapy. Warm water is obtained from burning fuels such as fossil fuel that is not environmentally friendly. Then technologies based on an alternative energy source is needed to be an optimal solution to the heating of a swimming pool, which can be very expensive in terms of energy demand and environment conservation. Due to the sizeable geothermal potential owned by Indonesia and only 3% of the total potential that has been successfully used for electricity generation (PLTP), therefore a design of a heated swimming pool heated by geothermal fluid was made to utilize clean and environmentally friendly energy sources in the Lembang region, West Java. The pool, which is designed to have an area of 10 x 10 m2, has a temperature of 26-30 oC and is heated by a geothermal fluid at a rate of 12.7 l/s and a temperature of 110 oC. The total heat energy utilized is 170 to 330 W/m2. Economic analysis shows an NPV of more than one and an IRR of 17% for a 10-year economic life. Hence, this warm swimming pool deserves to be developed.